Populist rhetoric in politics and media: A longitudinal study of the Netherlands. (December 2014) - Bos, Linda; Brants, Kees
Many claim that populism in the Netherlands has grown over the last 10 years; that it spreads among mainstream parties; that its success has to do with the media, who pay more and more attention to populist parties and immigration issues; but that it is difficult to distinguish between political populism intended for the media and populism by the media. In a longitudinal content analysis of newspapers, television news, talk shows and party political broadcasts, covering seven elections in nearly 20 years, these claims are put to the test. The picture that emerges is far more ambiguous than publicized opinion suggests, with no clear trend but a downward one in 2012.